THE ROLE OF CORRECTIONAL INSTITUTIONS IN EFFORTS TO FULFILL THE RIGHTS OF PRISONERS WITH DISABILITIES - Lauditta Indahdewi; Dimas Darmawan (Polteknik Ilmu Pemasyarakatan, 2021)
Prisoner is a person who is sentenced to a criminal sentence of loss of independence and serves it in a correctional institution. Therefore, it is the duty of the Government to protect and ensure the fulfillment of their rights while serving their sentence. This is a consequence of the imposition of criminal penalties which means limiting the right to freedom of movement. No exception for prisoners with disabilities. Therefore, this study will examine the role of correctional institutions in an effort to fulfill the rights of prisoners with disabilities with the research locus located in the Yogyakarta Class II-A Correctional Institution. This type of research is normative legal research with a juridical approach. The data collection techniques were carried out through secondary data which is literature with qualitative data analysis techniques. Based on the results of the study, it is known that Yogyakarta Class II-A Correctional Institution already fulfill the rights of prisoners with disabilities based on Undang-Undang No. 08 Tahun 2016 tentang Penyandang Disabilitas.